Directed growth of quinacridone chains on the vicinal Ag(35 1 1) surface - Humberg, Niklas; Grönwoldt, Lukas; Sokolowski, Moritz (Beilstein Journal of Nanotechnology, 2024)
The formation of self-assembled domains and chains of monomolecular width of quinacridone (QA) on the vicinal Ag(35 1 1) surface was investigated by scanning tunneling microscopy and low-energy electron diffraction. The focus was on the influence of the steps on the QA structures and their preferential azimuthal orientations with the aim of achieving a selective orientation. After deposition at a sample temperature of 300 K, QA forms the same kind of molecular chains as on the nominally flat Ag(100) surface because of strong intermolecular hydrogen bonds, which we reported in a previous publication [Humberg, N.; Bretel, R.; Eslam, A.; Le Moal, E.; Sokolowski, M. J. Phys. Chem. C 2020, 124, 24861–24873]. The vicinal surface leads to one additional chain orientation, which is parallel to the Ag step edges. However, most chains nucleate on the Ag terraces between steps with four distinct azimuthal orientations that are identical to those on Ag(100), and which are determined by the interactions with the (100) surface. At 300 K, the chains grow across the Ag steps, which do not break the azimuthal chain orientations. In contrast, during the deposition at sample temperatures of 400 and 500 K, the nucleation of the chains takes place at the Ag step edges. Hence, these have a strong influence on the azimuthal orientation of the molecules, resulting in a preferential growth of the chains in two of the four azimuthal orientations. We explain this by the adaptation of favorable adsorption sites, which involve the replacement of Ag atoms by QA molecules with specific azimuthal orientations at the step edges.
Keywords: Ag(100); intermolecular hydrogen bonds; one-dimensional aggregates; organic nanostructures; quinacridone; step-molecule interactions; vicinal surface